Pre-exposure immunization against rabies using Japanese rabies vaccine following the WHO recommended schedule - Yanagisawa, Naoki; Suganuma, Akihiko; Takayama, Naohide; Nakayama, Eiichi; Mannen, Kazuaki (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2010)
We examined the efficacy and safety of the Japanese purified chick embryo cell rabies vaccine (PCEC-K) when administered on days 0, 7, and 28, as recommended by the WHO. Post-vaccination serum samples were obtained from 53 human subjects, and rabies antibody titers were determined by a combination of enzyme-linked immunosorbent assay (ELISA) and neutralizing antibody (NA) assay. By day 42 of the experiment, which was 2 weeks after the third dose, all subjects had developed NA titers of 0.5IU/ml or higher. The geometric mean titers of ELISA antibody and NA were 3.8EU/ml and 5.7IU/ml, respectively. Overall, the vaccine was well tolerated by all subjects. These results suggest that PCEC-K used for pre-exposure immunization according to the WHO schedule is as immunogenic and effective as the current pre-exposure immunization regimen in Japan, which consists of vaccines administered on days 0, 28, and 180. An accelerated schedule would be of great advantage to Japanese travelers, who could complete the required three doses for primary immunization in 1 month.